Psychopathology—a Precision Tool in Need of Re-sharpening - Schultze-Lutter, Frauke; Schmidt, Stefanie J.; Theodoridou, Anastasia (Frontiers in Psychiatry, 2018)
Psychopathology is the scientific exploration of abnormal mental states that, for more than a century, has provided a Gestalt for psychiatric disorders and guided clinical as well as scientific progress in modern psychiatry. In the wake of the immense technical advances, however, psychopathology has been increasingly marginalized by neurobiological, genetic and neuropsychological research. This ongoing erosion of psychiatric phenomenology is further fostered by clinical casualness as well as pressured health care and research systems. The skill to precisely and carefully assess psychopathology in a qualified manner used to be a core attribute of mental health professionals, but today’s curricula pay increasingly less attention to its training, thus blurring the border between pathology and variants of the “normal” further. Despite all prophecies that psychopathology was doomed, and with neurobiological parameters having yet to show their differential-diagnostic superiority and value for differential indication, psychiatric diagnosis continues to rely exclusively on psychopathology in DSM-5 and ICD-11. Their categorical systematic, however, is equally challenged, and, supported by advances in machine learning, a personalized symptom-based approach to precision psychiatry is increasingly advocated. The current paper reviews the objectives of psychopathology and the recent debate on the role of psychopathology in future precision psychiatry – from guiding neurobiological research by relating neurobiological changes to patients’ experiences to giving a framework to the psychiatric encounter. It concludes that contemporary research and clinic in psychiatry do not need less but rather more differentiated psychopathologic approaches in order to develop approaches that integrate professional knowledge and patients’ experience.